New media technologies: public mobilization in political goals (Herald of Journalism, 2016)
The mass media technologies of “information wars”, “velvet” revolutions, ethnic mobilization, receptions of effective psychological impact on the audience, behavior changing strategy are fulfilled that inevitably raises at the state level the question of information security, access to information resources. The mass media incorporated in the power practically erase sides between political and information activities. The effective technologies directed on interaction of representatives of power structures, political elite, financial groups with journalists and information structures, allow to fulfill in practice of mass media of model of this interaction (model of “conflict”, “crisis”, “accident”, “chaos”, “system”, “market”, “game”, “competition”, “cooperation”, “partnership”, “bargaining”, “a public and collective choice”, “power interception”). Today mass media can provoke actions of broad national movement of new type which sees sense and the purpose of the existence “not in race for power, and in fight against the power”.
Keywords: information security; conflict; crisis